(untitled) (World Bulletin of Management and Law, 2022)
This article discusses proposals and recommendations for the implementation of reforms in the field of public service, the importance of the Constitution in the organization of public service, constitutional principles and their implementation, the relationship between public service and public civil service, the essence of the draft law “On public civil service” the role Constitutions in the creation of public service.